2005
DOI: 10.1124/dmd.105.005330
|View full text |Cite
|
Sign up to set email alerts
|

FORMATION OF TAMOXIFEN-DNA ADDUCTS VIA O-SULFONATION, NOT O-ACETYLATION, OF α-HYDROXYTAMOXIFEN IN RAT AND HUMAN LIVERS

Abstract: ABSTRACT:Tamoxifen (TAM) is used as the standard endocrine therapy for breast cancer patients and as a chemopreventive agent for women at high risk for this disease. Unfortunately, treatment of TAM increases the incidence of endometrial cancer; this may be due to the genotoxic damage induced by TAM metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Tamoxifen is used as the standard adjuvant endocrine therapy for breast cancer patients and as a chemopreventive agent for women at high risk for the disease (34). The increased incidence of endometrial cancers in patients treated with tamoxifen has been attributed to genotoxic damage induced by tamoxifen-DNA adducts after O-sulfation of tamoxifen by SULT (35). To our knowledge, AF is the only reported anticancer agent for which activation by SULTs is required for its therapeutic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen is used as the standard adjuvant endocrine therapy for breast cancer patients and as a chemopreventive agent for women at high risk for the disease (34). The increased incidence of endometrial cancers in patients treated with tamoxifen has been attributed to genotoxic damage induced by tamoxifen-DNA adducts after O-sulfation of tamoxifen by SULT (35). To our knowledge, AF is the only reported anticancer agent for which activation by SULTs is required for its therapeutic activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, sulfonation is not always beneficial, and tamoxifen, which is used in treating breast cancer, provides an example of a drug where sulfonation has been suggested to be important for the development of an associated adverse reaction, namely an increased incidence of endometrial cancer. Thus, it has been suggested that tamoxifen-DNA adducts are formed via O-sulfonation (56). As a further example, sulfonation phenotype could potentially influence both the efficacy and side-effects of apomorphine, for which sulfonation is the major metabolic pathway in humans (57).…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to determine whether tamoxifen therapy can lead to DNA adducts in the human endometrium have yielded conflicting results (Greaves et al, 1993;Hemminki et al, 1996;Carmichael et al, 1999;Shibutani et al, 2000;Sharma et al, 2003b;Beland et al, 2004). Studies in experimental model systems suggest that sulfation of ␣-hydroxylated tamoxifen metabolites mediates DNA adduct formation (Shibutani et al, 1998;Kim et al, 2005a). In addition, covalent binding to proteins and to 2Ј-deoxyguanosine via CYP3A4 and/or CYP2D6 catalyzed formation of 3,4-dihydroxytamoxifen, and subsequent bioactivation has been reported in human and rat liver microsomes (Dehal and Kupfer, 1999).…”
mentioning
confidence: 99%